Sol-Gel Synthesis and Luminescence Properties of ZnMoO4:Tb3+ Nano-Structural Materials - Zhang, Jianfu; Zhang, Hui; Yang, Hu; Ling Wang, Zhen (Asian Journal of Chemistry, 2013)
The ultraviolet excitation molybdates-based green phosphors were synthesized by sol-gel method and characterized by X-ray powder diffraction, photoluminescence spectrum, UV-visible absorption spectrum and scanning electron microscopy. A systematic study about the effects of calcinations temperature on the composition and luminescent properties of the phosphors has also been undertaken. The result of XRD reveals that the ZnMoO4: Tb3+ phosphors have triclinic structure of bulk ZnMoO4. Under the excitation of 275 nm, the emission intensity of the self-activation phosphor MoO42– is weaken greatly, while that of Tb3+ 5D4®7F5 transition at 543 nm (green light) is significantly enhanced. These observed luminescent properties of this phosphor demonstrate it has potential applications as luminescent material in lighting, display, etc.